Maturational timing, physical self-perceptions and physical activity in UK adolescent females: investigation of a mediated effects model. (18th May 2020) - Cumming, Sean P; Harrington, Deirdre M; Davis, Melanie J; Edwardson, Charlotte L; Gorely, Trish; Khunti, Kamlesh; Rowlands, Alex V; Yates, Thomas; Sherar, Lauren B
Abstract: Background: Advanced (early) biological maturation may be a risk factor for inactivity among adolescent girls. Aim: To test the mediational effects of body attractiveness and physical self-worth on the relationship between biological maturity and accelerometer assessed moderate-to-vigorous physical activity (MVPA) in a large multi-ethnic sample of girls from the Midlands area in the UK (11–14 years). Subjects and methods: Biological maturity (predicting age at peak height velocity (APHV)); self-perceptions of body attractiveness, physical self-worth, and minutes spent in MVPA were assessed in 1062 females aged 11–14 years. Results: Structural equation modelling using maximum likelihood estimation and boot- strapping procedures supported the hypothesised model. Later maturation predicted higher perceptions of body attractiveness ( β = 0.25, p < .001) which, in turn, predicted higher perceptions of physical self-worth ( β = 0.91, p < .001) and, significantly higher MVPA ( β = 0.22, p < .001). Examination of the bootstrap-generated bias-corrected confidence intervals suggested that perceptions of body attractiveness and physical self-worth partially mediated a positive association between predicted APHV and MVPA ( β = 0.05, p < .001). Conclusions: Greater biological maturity (i.e. early maturity) in adolescent girls is associated with less involvement in MVPA and appears to be partly explained by lower perceptions of body attractiveness and physical self-worth. Physical activity interventions should consider girls' perceptions of their pubertal related physiological changes during adolescence, particularly among early maturing girls.